POLLEN STORAGE AND VIABILITY OF TWELVE CITRUS GENOTYPES IN BALI, INDONESIA - Ida Ayu Astarini (Scripta Biologica, 2019)
The aim of this research was to obtain a method for pollen storage of Citrus species in Bali. Pollen from 12 Citrus genotypes was collected from five different regions; Petang, Plaga, Kintamani, Besakih, and Payangan Village.  Pollen from intact anthers were stored at three different storage temperatures, i.e., 25oC (room temperature), 4oC (refrigerator), and -20oC (freezer), with or without oven dried at 40oC for 20 hours before storage.  Pollen viability was determined using in vitro germination test.  Germination media contained 20 g/l sucrose and 8 g/l agar.  Result shows that -20oC was the best storage temperature.  At this temperature, only slight reduction of pollen viability after 2 months storage.  Storage at room temperature (25oC – 30oC) was not effective; pollen was infected with fungus within a week of storage. Oven dried pre-treatment before storage made better performance on pollen stored at 4oC.  Pollen moisture content decreased after oven dried, which also decreased fungus infection.  Storage of pollen is an important aspect to plant breeding programs, when individuals to be hybridized do not flower at the same time or are geographically separated.  This is the first report on pollen storage and viability of Citrus genotypes grown in Bali.